If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = b + 1 + -1ax Reorder the terms: 2x = 1 + -1ax + b Solving 2x = 1 + -1ax + b Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'ax' to each side of the equation. ax + 2x = 1 + -1ax + ax + b Combine like terms: -1ax + ax = 0 ax + 2x = 1 + 0 + b ax + 2x = 1 + b Reorder the terms: -1 + ax + -1b + 2x = 1 + b + -1 + -1b Reorder the terms: -1 + ax + -1b + 2x = 1 + -1 + b + -1b Combine like terms: 1 + -1 = 0 -1 + ax + -1b + 2x = 0 + b + -1b -1 + ax + -1b + 2x = b + -1b Combine like terms: b + -1b = 0 -1 + ax + -1b + 2x = 0 The solution to this equation could not be determined.
| x-7y=34 | | 6x+6-2x=0 | | 6-7a-5a^2=0 | | 8-(1-2m)=8+2(4m-3) | | 3x^4+4x^2+28x+5=0 | | 11x+7=4x+56 | | 5(x+3)-2=2-x+9 | | 2y^2-8y=540 | | 8x-5y=-37 | | 4m+100=68 | | ln(7-3x)=7.5 | | -6-2n=48 | | V^2=4v-13 | | 5=15x-12y | | 7x-y=66 | | -2x+-8+-7x+2= | | -3x+2y=-33 | | (x*x)+18x+5=0 | | 225-6x=30x+17 | | h=-16t^2+80t+6 | | f(x)=-0.5x^3+2.5x^2+2x-10 | | 6.4x-3.5x=-46.4 | | -5g-7=3 | | -2n-15=61 | | f(x)=x^2+5x-2(2f(2)) | | f(x)=x^2+5x-2 | | 6+10x=42 | | [2-5(6+11)]= | | -4x+9y=-27 | | -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 |